2020
DOI: 10.1186/s12883-020-01967-y
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage: who gets tested for methamphetamine use and why might it matter?

Abstract: Background Methamphetamine use is an emerging risk factor for intracerebral hemorrhage (ICH). The aim of this study was to investigate the use of urine drug screen (UDS) for identifying methamphetamine-associated ICH. Methods This is a retrospective, single-center study of consecutive patients hospitalized with spontaneous ICH from January 2013 to December 2017. Patients were divided into groups based on presence of UDS. The characteristics of patients with and without UDS were compared. Factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…14 Conflicting data exist regarding whether Black patients are more likely or not to be screened for drugs of abuse after ICH compared with White patients. 15,16 One retrospective study found that male patients with ICH were more likely than female patients with ICH to undergo urine drug screening. 16…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…14 Conflicting data exist regarding whether Black patients are more likely or not to be screened for drugs of abuse after ICH compared with White patients. 15,16 One retrospective study found that male patients with ICH were more likely than female patients with ICH to undergo urine drug screening. 16…”
Section: Resultsmentioning
confidence: 99%
“…15,16 One retrospective study found that male patients with ICH were more likely than female patients with ICH to undergo urine drug screening. 16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…93.3%, respectively [26]. Cardiomyopathy was defined with reduced left ventricular ejection fraction to 45% or less on clinical echocardiography report [18].…”
Section: Introductionmentioning
confidence: 99%